Specific inhibitors of urokinase plasminogen activator for treatment of cancers; In silico approach - Talbot, Benjamin; Jankun, Jerzy (Translation: The University of Toledo Journal of Medical Sciences, 2020)
Invasion, metastasis and angiogenesis are fundamental processes in the development of solid cancers. All these depend on the proteolysis where plasminogen activation system (PAS) is the prominent component. Plasmin of PAS, with a broad spectrum of proteins lysed, is secreted as a pro-enzyme and then activated by urokinase (uPA) or tissue plasminogen activator (tPA). Urokinase is in control of pericellular proteolysis while tPA mediates intravascular fibrinolysis. The most effective way to reduce excessive activity of plasmin in cancers is by inactivation of its activators (PAs). Inhibition of PAs reduces tumor size of cancers in vivo. However, for successful targeted anticancer therapy it is essential to find specific uPA inhibitors and to protect normal function of tPA. Unfortunately, most known inhibitors are unspecific, acting on both PAs. PAs are highly homologous enzymes with extreme similarities in their active sites so large numbers of chemicals need to be tested to find novel specific uPA inhibitors. Methods: As the availability of 3D protein structures determined experimentally by X-ray crystallography is growing, computational methods are ever more used in targeted drug discovery. AutoDock Vina molecular docking, exploring binding of small molecules to target protein using a Monte Carlo technique and scoring function, is gaining popularity due to its excellent prediction accuracy. Results: Using AutoDock we have found many inhibitors of PA from our 3D database of 6170 compounds which bind in silico to X-ray structures of the specificity pocket (B187-B197, B212-B229) of both PAs preventing activation of plasminogen. However we were successful in identifying a few molecules which are specific for uPA. For example: both amiloride and chrysin bind to the specificity pocket of uPA but not to tPA. We have found that they bind to other parts of tPA, distant from the specificity pocket, thus preserving the tPA enzymatic activity while being effective toward uPA. Conclusion: In silico search yield specific inhibitors of uPA which, when verified for safety and efficiency by in vivo testing, could be used as novel therapeutics to limit metastasis and angiogenesis in anticancer therapy.